Optimizing post-thoracotomy pain management: comparing erector spinae vs. paravertebral block in thoracotomy patients: a prospective randomized study - Kerem Baser; Ozal Adiyeke; Ergun Mendes; Funda Gumus Ozcan (BMC Anesthesiology)
Abstract Background Postoperative pain can lead to serious complications in the short and medium term. It may also increase the risk of converting acute pain into chronic pain, leading to the development of postthoracotomy pain syndrome (PTPS). The aim of this study was to demonstrate the effectiveness of erector spinae plane block (ESPB) and paravertebral block (PVB) in managing acute postoperative pain and preventing the development of PTPS in patients undergoing thoracotomy and lobectomy. Methods This prospective, randomized study included American Society of Anesthesiologists (ASA) class II-III patients aged 18–70 years who underwent elective unilateral lobectomy via a thoracotomy. The study was conducted at Başakşehir Çam and Sakura City Hospital, following approval from the hospital’s ethics committee on May 20, 2022 (protocol number: KAEK.2022.05.155). Patients were randomly assigned into ESPB (n = 30) and PVB (n = 30) groups using a computer-generated randomization sequence prior to surgery. Intravenous patient-controlled analgesia (PCA) was provided for 24 h postoperatively. Resting numerical rating scala (NRS) and Prince Henry Hospital Pain Scale (PHHPS) scores were evaluated at 0, 2, 6, 12, and 24 h after surgery. Pain levels were further assessed via telephone interviews using the NRS at 2 weeks and 2 months postoperatively. Results The baseline NRS score was significantly lower in the PVB group (3.97 ± 0.61) compared to the ESPB group (4.37 ± 0.85) (p = 0.044). The mean number of PCA requests, mean opioid consumption and number of patients receiving rescue analgesics were significantly lower in the PVB group than in the ESPB group (p < 0.05). No significant differences were observed between the groups in hemodynamic parameters (p > 0.05). PTPS developed in 3 patients (1 in PVB, 2 in ESPB), with no significant intergroup difference (p = 0.561). Conclusions PVB and ESPB provided effective acute pain control after thoracotomy, with PVB showing superior outcomes in analgesic use and pain scores. Early management of postoperative pain may improve short-term recovery and potentially reduce PTPS incidence, which was 5% in our study—lower than reported in the literature. Trial registration ClinicalTrials.gov (ID NCT06964698). The clinical trial was retrospectively registered on April 02, 2025.